2002
DOI: 10.1152/ajpendo.00439.2001
|View full text |Cite
|
Sign up to set email alerts
|

MSG lesions decrease body mass of suckling-age rats by attenuating circadian decreases of energy expenditure

Abstract: Schoelch, Corinna, Thomas Hü bschle, Ingrid Schmidt, and Barbara Nuesslein-Hildesheim. MSG lesions decrease body mass of suckling-age rats by attenuating circadian decreases of energy expenditure. Am J Physiol Endocrinol Metab 283: E604-E611, 2002. First published April 23, 2002 10.1152/ajpendo.00439.2001.-Suckling-age rats display endogenous circadian rhythmicity of metabolic rate (MR) with energy-saving, torpor-like decreases, which are sympathetically controlled and suppressed by leptin treatment. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The onset of obesity is associated with low sympathetic and high parasympathetic activities to sustain the accumulation of energy sources, such as fat tissue, decreasing catabolism, and increasing anabolism. Regarding the BW of MSG rats, we observed that they were lighter than respective control animals, which was the characteristic phenotype of this model as described by Remke et al (1988), Dolnikoff et al (2001), and Schoelch et al (2002). Although there were no overweight rats, the MSG-obese rats were found to have more fat pad stores as compared with control animals (Bernardis & Patterson 1968, Bray & York 1998, which was correlated with lower growth hormone (Bakke et al 1978, Acs et al 1982 and reduced basal metabolic rate (Arndt et al 1991).…”
Section: Discussionmentioning
confidence: 67%
“…The onset of obesity is associated with low sympathetic and high parasympathetic activities to sustain the accumulation of energy sources, such as fat tissue, decreasing catabolism, and increasing anabolism. Regarding the BW of MSG rats, we observed that they were lighter than respective control animals, which was the characteristic phenotype of this model as described by Remke et al (1988), Dolnikoff et al (2001), and Schoelch et al (2002). Although there were no overweight rats, the MSG-obese rats were found to have more fat pad stores as compared with control animals (Bernardis & Patterson 1968, Bray & York 1998, which was correlated with lower growth hormone (Bakke et al 1978, Acs et al 1982 and reduced basal metabolic rate (Arndt et al 1991).…”
Section: Discussionmentioning
confidence: 67%
“…It leads to degeneration of the neurons in the arcuate nucleus, inner retinal layers and various other brain areas (Olney, 1969;Arees and Mayer, 1970;Heiman and Ben-Jonathan, 1983;van Rijn et al, 1986;Kubo et al, 1993;Ishikawa et al, 1997;Gonzalez-Burgos et al, 2001;Beas-Zarate et al, 2002;Chaparro-Huerta et al, 2002;Pesini et al,. 2004;Stricker-Krongrad and Beck, 2004;Tamas et al, 2004), along with endocrinological, neurochemical and circadian alterations (Lengvari, 1977;Dawson and Lorden, 1981;Miyabo et al, 1985;Mistlberger and Antle, 1999;Schoelch et al, 2002;Urena-Guerrero et al, 2003;Kim et al, 2005). The neurotoxicity of MSG is also reflected in various changes in the motor activity, sensory performance and learning abilities (Iwata et al, 1979;Saari et al, 1990;Fisher et al, 1991;Dubovicky et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…ARC MSG lesions have been successfully produced in Siberian hamsters, demonstrating that SP-induced changes in hamster body mass, food intake, fur color, and testis mass persist after ARC ablation (16). If MSG ablations in Siberian hamsters mimic the effect on circadian T b min in suckling rat pups (45), then ARC MSG ablations should eliminate photoperiod-dependent torpor in hamsters. Differ-ences in fat reserves between MSG-and saline-treated hamsters raised in SPs were previously nonsignificant (16).…”
mentioning
confidence: 97%
“…7 and 26), especially targeting ARC neuropeptide Y and proopiomelanocortin neurons, which both colocalize leptin receptors but have opposing effects on metabolism (9,26,31). MSG ablation of the ARC eliminates "torpor-like" circadian decreases in T b in suckling rats (45).…”
mentioning
confidence: 99%